Impact of Health Education on Improving Knowledge of Dysmenorrhea Among Nursing Students - Ema Kusumawati; Ervina Kurniawati; Sherly Yunita (Presscience, 2025)
Dysmenorrhea, characterized by menstrual pain, is a common condition experienced by many young women, typically manifesting as cramping and localized in the lower abdomen. The intensity of dysmenorrhea is often influenced by the duration and volume of menstrual flow. One effective strategy to improve understanding of this condition is through Health Education. This study aims to assess the impact of Health Education on the knowledge of dysmenorrhea among female nursing students at Muhammadiyah University Klaten, particularly those in their third year of the S1 Nursing program. The research utilized a Quasi-Experimental design with a one-group pre-test/post-test structure. Health Education sessions were conducted via Zoom, and 10 students participated in the study. Knowledge levels were evaluated using pre- and post-test questionnaires. Before the Health Education intervention, 70% of the participants had limited knowledge about dysmenorrhea, while following the education session, knowledge levels increased significantly to 86.7%. The findings indicate a substantial improvement in the participants' understanding of dysmenorrhea and strategies for managing menstrual pain.